The development of an incremental debugging system : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Computer Science at Massey University - McDonald, Malcolm John (Massey University, 1978)
Debugging is a major area of software development that has received little attention. This thesis starts by looking at work done in the area of bug prevention, bug detection, bug location and bug correction. A debugging system, BIAS, is proposed to help in detecting, locating and correcting bugs. Three major design goals are established. Firstly, the system should be simple and easy to understand as this will encourage use. Secondly, the system should be general so that it will be available to a large number of users. Finally, it should be incremental as this will save users' time. An incremental language, STILL, is designed to show how BIAS applies to structured languages. The construction of the system is shown. Each data structure, and how it is used, is described. BIAS uses an interpretive system and runs threaded code on a pseudo-machine. How the threads are interpreted and how they are set up is shown next. The use of BIAS is shown by following through an example session with the system. This consists of entering a program, editing it, and running it. As bugs show themselves, various debugging commands are used to locate the bugs. The program is then edited, and the corrections linked into the code so that it will run correctly. This cycle is repeated until no bugs remain, without at any time recompiling the whole program. It turns out that the best way of achieving the design goals is to extend an incremental compiler host to include debugging commands. This gives a clear emphasis to the power of incremental compilers.
Keywords: Computer software -- Development; Debugging in computer science